Preparation and Drug-Loading Properties of Amphoteric Cassava Starch Nanoparticles - Xinling Xie; Youquan Zhang; Yong Zhu; Yiling Lan (Nanomaterials, 2022)
Based on the characteristics of charge reversal around the isoelectric point (pI) of amphoteric starch-containing anionic and cationic groups, amphoteric cassava starch nanoparticles (CA-CANPs) are prepared by a W/O microemulsion crosslinking method using (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride as a cationic reagent and POCl3 as an anionic reagent, and the effects of preparation conditions on the particle size of the CA-CANPs are studied in detail in the present study. CA-CANPs with a smooth surface and an average diameter of 252 nm are successfully prepared at the following optimised conditions: a crosslinking agent amount of 15 wt%, an aqueous starch concentration of 6.0 wt%, an oil–water ratio of 10:1, a total surfactant amount of 0.20 g·mL−1, and a CHPTAC amount of 4.05 wt%. The pH-responsive value of the CA-CANPs can be regulated by adjusting the nitrogen–phosphorus molar ratio in the CA-CANPs. By using CA-CANPs with a pI of 6.89 as drug carriers and the paclitaxel (PTX) as a model drug, the maximum loading rate of 36.14 mg·g−1 is achieved, and the loading process is consistent with the Langmuir isotherm adsorption, with the calculated thermodynamic parameters of ΔH° = −37.91 kJ·mol−1, ΔS° = −10.96 J·mol−1·K−1 and ΔG° < 0. By testing the release rate in vitro, it is noted that the release rates of PTX in a neutral environment (37.6% after 96 h) and a slightly acidic environment (58.65% after 96 h) are quite different, suggesting that the CA-CANPs have the possibility of being a targeted controlled-release carrier with pH responsiveness for antitumor drugs.